Fecundity Indices of an Endangered Indigenous Carp, Labeo dussumieri (Val.), of Kerala - B., Madhusoodana Kurup; Kuriakose, Binu (Fishery Technology, 2025)
The absolute fecundity of Labeo dussumieri (Val.) varied from 66,420 to 2,39,854 eggs in specimens ranging in total length from 294.5 to 437.0 mm. The relative fecundity varied from 91 to 254 ova while the number of ova per gram ovarian weight ranged from 806 to 1791. The coefficient of maturity was found to vary from 13.3 to 26.8 and the gonosomatic index from 11.5 to 35.9. The fecundity of L. dussumieri in relation to fish length, fish weight, ovary length and ovary weight are worked out using regression analysis. By comparing the average values of relative fecundity and number of ova per gram ovarian weight of L. dus- sumieri with those of other Labeo spp. of India it could be seen that the former produces less number of ova, when compared to the latter.